Business Model Canvas dalam Menentukan Strategi Usaha Saprotan yang Efektif - Nurwati, Ucu (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Business Models Canvas is an effective tool for describing, assessing and determining business strategy by referring to nine main elements, namely: Customer Segments, Value Propositions, Channels, Customer Relationships, Revenue Streams, Key Resources, Key Activities, Key Partnerships, dan Cost Structure.This strategy is prepared by knowing the strengths, weaknesses, opportunities and threats through the IFAS, EFAS, and SWOT matrices. The method used in this research is a case study. The data obtained was carried out through interviews, questionnaires, observations and literature studies which werw then analyzed descriptively. The respondent sampled in this research werw 36 farmer members of the cooperative. The results of this research are the knowledge of the strengths, weaknesses, opportunities and threats that are owned and faced by the Sumber Tani Mandiri Agricultural Cooperative, where the results are used to determine an effective business strategy to increase the sales volume of inputs. By using BMC, cooperatives can develop more effective business strategies to improve their performance and competitiveness. Strategy recommendations include improving financial recording systems, product diversification, improving customer service, and utilizing marketing information technology.